2018
DOI: 10.1016/j.anai.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive biomarker studies in eosinophilic esophagitis

Abstract: Several promising minimally invasive biomarkers for EoE have emerged; however, few are able to differentiate EoE from other atopic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 66 publications
(29 reference statements)
3
48
0
4
Order By: Relevance
“…Multiple surrogate biomarkers of EoE disease activity have been examined over the years, and this topic has been reviewed recently. 105,106 Numerous studies have identified promising esophageal tissue biomarkers, including differential expression of cytokines, chemokines, mast cells, and other factors in esophageal mucosal biopsies from patients with EoE compared with control subjects. [107][108][109][110][111] Mucosal impedance, measured with a variety of techniques including stationary, probe-and balloon-based, is also promising and may distinguish EoE from controls and track with histologic disease activity.…”
Section: Range Of Potential Outcomes In Eoementioning
confidence: 99%
“…Multiple surrogate biomarkers of EoE disease activity have been examined over the years, and this topic has been reviewed recently. 105,106 Numerous studies have identified promising esophageal tissue biomarkers, including differential expression of cytokines, chemokines, mast cells, and other factors in esophageal mucosal biopsies from patients with EoE compared with control subjects. [107][108][109][110][111] Mucosal impedance, measured with a variety of techniques including stationary, probe-and balloon-based, is also promising and may distinguish EoE from controls and track with histologic disease activity.…”
Section: Range Of Potential Outcomes In Eoementioning
confidence: 99%
“…Two unmet needs are to more precisely and objectively diagnose EG and develop monitoring tools for disease Abbreviations used AUC: Area under the curve CCHMC: Cincinnati Children's Hospital Medical Center CEGIR: Consortium of Eosinophilic Gastrointestinal Disease Researchers CT: Cycle threshold EG: Eosinophilic gastritis EGDP: EG Diagnostic Panel EGID: Eosinophilic gastrointestinal disorder EoE: Eosinophilic esophagitis FDR: False discovery rate GAPDH: Glyceraldehyde-3-phosphate dehydrogenase hpf: High-power field IL-4R: IL-4 receptor ROC: Receiver operating characteristic TARC: Thymus and activation-regulated chemokine TSLP: Thymic stromal lymphopoietin management and clinical trial readiness. 18,19 Circulating biomarkers have the potential to facilitate noninvasive disease diagnosis and monitoring and represent a pressing need in the field. Previous studies suggest that EG has potential systemic markers, such as concurrent peripheral blood eosinophilia.…”
mentioning
confidence: 99%
“…In a proof of concept study, urine 3-Bromotyrosine (3-BT) differed between EoE and atopic and nonatopic controls. 10,11 Other tests being studied for diagnosis and long-term monitoring of EoE include esophageal string test and swallowed cytosponge test, which can potentially serve as minimally invasive tools to assess disease activity; initial data show good correlation with esophageal eosinophilia. Unsedated in-office transnasal endoscopy may provide another less invasive method for disease monitoring.…”
Section: Diagnosismentioning
confidence: 99%